Mastoid surgery outcomes in two tertiary Malaysian hospitals - Noor Azrin Md Anuar; Zara Nasseri; Azila Alias; Noor Dina Hashim; Farah Liana Lokman; Azmi Mohd Tamil; Asma Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2021)
Objective: Mastoidectomy is a surgical procedure of exenterating the mastoid air cell. The goal of this surgery is to create a dry, safe ear, to preserve or restore functional hearing as much as possible and to prevent complications. There are two types of mastoidectomy, each with their own indications, advantages, and disadvantages. It can be divided into canal wall up mastoidectomy (CWUM) and canal wall down mastoidectomy (CWDM). The objective of this study is to determine the outcome of both types of mastoidectomy in term of audiological and ear status for patients with chronic active otitis media (OM) with cholesteatoma, chronic mastoiditis or chronic active OM with cholesteatoma and mastoiditis managed at our tertiary centres; Universiti Kebangsaan Malaysia Medical Centre (UKMMC) and Kuala Lumpur General Hospital (KLGH). Design: A retrospective 10-year study was conducted at UKMMC and KLGH. Materials & Methods: All patients who were diagnosed with CSOM with / without cholesteatoma and/ or chronic mastoiditis and underwent surgical intervention during the study periods were included in this study. The age, gender, presenting symptoms, complications, diagnosis, surgical procedures and the surgical findings were retrieved from clinical notes. The postoperative pure tone audiometric (PTA) thresholds were evaluated on the follow-up visit within six months to one year after surgery. Results: There were 253 patients recruited with 260 ears as study samples. 103 cases underwent CWUM and 157 cases underwent CWDM. At surgery, cholesteatoma was detected in 68% of the patients. We found 58.3% of ears in the CWUM group showed improvement in hearing threshold whereas only 44.6% showed improvement in the CWDM group. Post-operatively, mean PTA in CWUM (49.7dB) is significantly better than CWDM (59.2dB) with p value of 0.003. In CWUM, the mean air bone gap (ABG) is 24.05dB, which is significantly better than in CWDM (31.03dB). From all patients who underwent CWUM, 42% had post-operative ABG less than 20dB and this only occurred in 20.6% of the CWDM group. For ear status, 85% of patients who underwent CWUM had a dry ear postoperatively, which is significant compared to CWDM which was 69%. Conclusion: CWUM provides a better hearing outcome based on average air conduction (AC) threshold, AC gain and mean ABG. It also has a higher chance of obtaining a safe, dry ear.